A brief systematic review of the single-case research on Prevent-Teach-Reinforce. - Gregori, Emily; Lory, Catharine; Smith, Sandy; Drew, Christine (International Journal of Developmental Disabilities, 2026)
This systematic literature review synthesizes the single-case research on Prevent-Teach-Reinforce (PTR). The purpose of the review was to evaluate the methodological quality, evidence, and descriptive characteristics of each included study. A systematic database search identified 12 studies that met inclusion for this review, including 21 unique experiments. Less than one quarter of the included experiments were shown to be methodologically rigorous based on the What Works Clearinghouse Version 5.0 standards. Of those experiments, most were shown to have strong or moderate evidence of efficacy for PTR on challenging and replacement behaviors. Major findings, limitations, and implications for practice are discussed.